Pengaruh Ekspresi Emosi Keluarga terhadap Frekuensi Kekambuhan Pasien Skizofrenia di Rumah Sakit Jiwa Daerah Surakarta - Irene Yunita Prihandini; Aris Sudiyanto; Ruben Dharmawan (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Schizophrenia is a severe disease, with basic personality disorder, distortion the proccess of thought, sometimes have the feeling that he/she was being controlled by external powers, peculiar delusions, disturbing perception, and an affect which does not correspond to the actual situation. In Schizophrenia patients, there are degradation in the field of employment, socialization, and self-care function. Thus, the patient requires caregiver who could take care of him/her, especially when the disease is relapse. Methods: This research is analitical observational by its character with the case control study approach that held between June up to July 2012 in Rumah Sakit Jiwa Daerah Surakarta. It used purposive sampling by divide it into two inclusion criterisa, the caregiver inclusion criteria were (1) Schizophrenia patient's family that accompany the patient in the Rumah Sakit Jiwa Daerah Surakarta (2) Schizophrenia patient's family that live in the same house with the patient (3) Patient that currently 20-60 years old (4) Voluntarily become respondent in this research and have agreed the informed consent sheet, whereas the inclusion criteria for the schizophrenia patients was (1) relapse patient (2) no reccurrence patient. The sample fulfill (1) identity & informed consent sheet (2) emotion expression quesioner. There are 60 sample and analyzed by pearson test and paired sampel t-test with SPSS 17.0 program for windows. Results: According to the result, we have known that the significance level is 0.004 so (which is 0.004<0.01/0.05) the decision is to accept the hypothesis which was stated that there is a significant connection between the emotion expression with the frequency of recurrence Schizophrenia patients in Rumah Sakit Jiwa Daerah Surakarta. The average difference between the groups of high emotional expression and low emotional expression, t arithmetic (3.826 > t table 1.76) so that H0 could be rejected. Therefore, there is also significant difference in recurrence between the groups of high emotional expression and the low emotional expression. While r calculation in this research is 0.058, so the alternative hypothesis (Ha) which was stated that there is significant positive connection between the Emotional Expression (EE) with the frequency of reccurrence Schizophrenia Patients in Rumah Sakit Jiwa Daerah Surakarta is accepted. Thus, naught hypothesis (Ho) which was stated that there isn't significant positive between the family emotional expression (EE) and the frequency of recurrence is rejected. The direction of both variables is positive, that is if Schizophrenia patient's family emotional expression is high then the frequency of recurrence must be high too, vice versa. Conclusions: The higher family emotional expression (EE) then the frequency of recurrence is must be higher too, vice versa. Key words: Emotional Expression, Frequency of Recurrence